2022
DOI: 10.1093/ecco-jcc/jjac175
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Recurrence or Anastomotic Wound Healing Phenomenon after Ileocolic Resection for Crohn’s Disease: The Challenges of Accurate Endoscopic Scoring

Abstract: Background and aims Adequate endoscopic scoring in Crohn’s disease (CD) is crucial, as dictates the need for initiating postoperative medical therapy and is utilized as outcome parameter in clinical trials. We aimed to observe anastomotic wound healing in relation to endoscopic scoring of both inverted and everted stapled lines in side-to-side anastomoses. Methods Two prospective patient cohorts were included: ileocolic resec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The different adaptation of the cut ends of the bowel determines the type of wound healing. Direct mucosa-to-mucosa adaptation in an everted anastomosis will result in primary wound healing, whereas the serosa-to-serosa adaptation of the longitudinal staple line will heal with secondary intent [ 31 ]. This secondary intent healing involves a process where the mucosa needs to re-epithelialize over the staple line.…”
Section: Discussionmentioning
confidence: 99%
“…The different adaptation of the cut ends of the bowel determines the type of wound healing. Direct mucosa-to-mucosa adaptation in an everted anastomosis will result in primary wound healing, whereas the serosa-to-serosa adaptation of the longitudinal staple line will heal with secondary intent [ 31 ]. This secondary intent healing involves a process where the mucosa needs to re-epithelialize over the staple line.…”
Section: Discussionmentioning
confidence: 99%
“… 96 Recently, we demonstrated that both patients with stapled anastomoses after resection for colorectal cancer and for CD show these ulcerations at 6 months after surgery. 97 These ulcerations might influence endoscopic scoring of recurrence and might lead to overscoring. In fact, when handsewn and Kono-S anastomoses are compared with stapled anastomoses, this normal wound healing phenomenon of the stapled anastomosis may even interfere with the diagnosis disease recurrence when assessing ER.…”
Section: Discussionmentioning
confidence: 99%